Effect of two different materials in sealing vertical root fractures of intentional replantation on epithelial thickness of periradicular tissue - Raphael Tri Endra Untara; Widjijono Widjijono; Widya Asmara; Diatri Nari Ratih (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Vertical root fractures of intentional replantation need a material capable of binding the fragments of the fracture line tightly and encouraging the regeneration of periradicular tissue. One of the indicators that regeneration of periradicular tissue takes place is epithelial thickness. This study aimed to investigate the effect of mineral trioxide aggregate (MTA) and self-adhesive resin cement as the adhesive materials in sealing vertical root fractures of intentional replantation on the epithelial thickness of periradicular tissue. This study used 27 male New Zealand rabbits with the age range of 8-12 weeks. The mandibular incisor was extracted, and the tooth was cut from the cervical border to the 2/3 apical third. The samples were assigned randomly into three groups of 9 each, namely Group 1 with no application of any material in the fracture line (control group), Group 2 with MTA, and Group 3 with self-adhesive resin cement. All the teeth in all the groups were then inserted back into the socket. Each group was further divided into three subgroups based on the observation time, namely days 7, 14, and 21. Histological observations of the epithelial thickness were carried out under the light microscope (400x magnification). Data were analyzed using a two-way ANOVA and LSD post hoc test with a confidence level of 95%. The two-way ANOVA analysis showed that the materials used for sealing the fracture lines had a significant effect on the epithelial thickness (p<0.05), while the observation time did not affect the epithelial thickness (p>0.05). No interaction occurred between the material used and observation times (p>0.05). It can be concluded that MTA generated a greater epithelial thickness of periradicular tissue compared than self-adhesive resin cement in sealing vertical root fractures of intentional replantation.